WOMAN LEADERSHIP IN THE QURAN - Hossain, Md. Kohinoor (International Journal of Shari’ah and Corporate Governance Research, 2022)
The paper asserts that Islam, as defined by the Quran and Ahsanool Hadith, advocates for equal rights and leadership opportunities for both men and women, challenging patriarchal interpretations. It highlights women’s historical leadership roles, especially in the early stages of civilization, with economic activities in their hands. The author critiques classical exegesis for perpetuating a patriarchal and misogynistic system and seeks to reinterpret Quranic teachings to establish gender equality in leadership. The text argues that men and women are equal in their capabilities and contributions, with women performing unique roles, such as childbearing and nurturing, that men do not share. The paper cites Quranic verses, Ahsanul Hadith, Ijma, and Qiyas, to support the claim that women can lead in various sectors independently, including society, education, family, economy, Culture, and religion. It applauds contemporary Muslim societies where women’s leadership is acknowledged. The author strongly criticizes groups like the Taliban, considering them divergent from Quranic teachings. The paper concludes by advocating for women’s leadership as a lawful and necessary demand, expressing hope that women can lead globally for future peace—a prospect aligned with Quranic ideals. The research aims to rediscover and promote women’s leadership in Islam, emphasizing its compatibility with Quranic principles and challenging patriarchal interpretations.